2018
DOI: 10.1364/ol.43.002078
|View full text |Cite
|
Sign up to set email alerts
|

Stretched graded-index multimode optical fiber as a saturable absorber for erbium-doped fiber laser mode locking

Abstract: A novel mode-locking method based on the nonlinear multimode interference in the stretched graded-index multimode optical fiber (GIMF) is proposed in this Letter. The simple device geometry, where the light is coupled in and out of the stretched GIMF via single-mode fibers, is demonstrated to exhibit the temporal intensity discrimination required for mode locking. The nonlinear saturable absorber (SA) characteristics of the device are controllable by simply adjusting the strength of the stretching applied. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Several different variants of the technique of fiber laser mode-locking based on nonlinear MMI have been demonstrated in recent years [16][17][18][19][20][21][22][23][24]. In order to test the nonlinear transmission of the SMS structure, the MMF was stretched, and the SMS transmission was measured as a function of the stretching length, for different input intensities [20]. It was found that, at relatively high intensities, the self-imaging induced beam oscillations occur with much smaller amplitude, and with average (i.e., over one self-imaging period) transmission that is significantly increased ( 75%) with respect to the low intensity case ( 68%).…”
Section: Introductionmentioning
confidence: 99%
“…Several different variants of the technique of fiber laser mode-locking based on nonlinear MMI have been demonstrated in recent years [16][17][18][19][20][21][22][23][24]. In order to test the nonlinear transmission of the SMS structure, the MMF was stretched, and the SMS transmission was measured as a function of the stretching length, for different input intensities [20]. It was found that, at relatively high intensities, the self-imaging induced beam oscillations occur with much smaller amplitude, and with average (i.e., over one self-imaging period) transmission that is significantly increased ( 75%) with respect to the low intensity case ( 68%).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, graded-index multimode fiber (GIMF) was demonstrated to act as SA in an erbium-doped fiber laser by G. Chen [13]. By stretching the GIMF, controllable modulation depth of the SA device was achieved as the length of GIMF is a crucial parameter in NL-MMI [14]. In order to circumvent this limitation, step-index multimode fiber (SIMF) [15] and non-core fiber (NCF) [16] were proposed to expand the diameter of mode field, thus optimizing the performance of the NL-MMI based mode-locking.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] In 2017, Wang realized saturable absorption characteristics by stretching SMS, and the stable mode‐locking was experimentally obtained at the central wavelength of 1572.5 and 1591.4 nm. [ 23 ] The next year, Yang reported soliton observations based on SMS system, which introduced an inner microcavity into GIMF as a nonlinear optical switch. [ 24 ] Our group has also carried out some research in related areas.…”
Section: Introductionmentioning
confidence: 99%